Ornamentos de platibanda em edificações de Belém entre os séculos XIX e XX: inventário e conservação - ARRUDA, Tainá Chermont (Universidade Federal do Pará, 2019)
The vitrified ceramic ornaments were used as decorative elements and pieces such as statues, had allegorical paper in the crowning of the facades to highlight or to characterize the typological function of the building or as a symbol that the owner wanted to convey referring to the values defended at the time of the Industrial Revolution. The ornaments on the platibands formed a set of pieces with allegorical meanings, which symbolized wealth and erudition, to be attributed to the elite, since the Modern era. The objective of this research was to identify the ornaments made of glazed ceramic that make up the eclectic architecture of the Historic Center of Belém (Pará) and its surroundings with a view to tracing subsidies for its preservation. We sought to identify and locate the types of vitrified ornaments existing in the Historic Center and its surroundings of the city of Belém do Pará, through a visual inspection of the region, making it possible to analyze and understand the context of these pieces in the local reality. A total of 225 properties with ornamental plaice were identified in the analyzed area. The use of textual documents, printed catalogs, newspapers and albums of the 19th and 20th century was used to support research and identification of ornaments. Vitrified ceramic ornaments suffer an accelerated process of disappearance because they are exposed in the building panels, since they are more vulnerable to intemperate action, be it physical, chemical or mineralogical, and anthropic action, including acts of vandalism. These glazed ceramic ornaments are important examples of the cultural heritage of Belém, as they are evidence of the European influence in the region, more specifically Portuguese, besides being products of technical development of the material and symbolic of the nineteenth century, which deserve urgent preservation actions.